(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article discusses the advantages of innovative techniques in the formation of a new high-quality education in higher educational institutions. Introduction of innovative technologies into the educational process plays a major role in training of well-educated, intellectual and socially active specialist. The main objective of Al-Farabi University is to produce spiritually mature, highly cultured personalities. The methods of innovative technologies in the theory of teaching of the Kazakh language are developed. It also describes the types of technology and methods of teaching, and their innovative features. One of the innovative features is the «step by step» complex of technologies. «Step by step» complex of technologies implies a complete mastery of teaching methods and means of gaining knowledge, based on a scientific, qualitative and systematic approach, the ability to evaluate the national values and motivation of students to use them in their professional activity.